PENGARUH CELEBRITY ENDORSER DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA SMARTPHONE OPPO DI BEC BANDUNG - Joan Yuliana Hutapea; Gena Gemasta Barus (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2022)
The purpose of this study is to determine the influence of Celebrity Endorser and Price on Purchase Decision of Oppo Smartphone at BEC Bandung. The data used in this study were the primary and secondary data. Primary data were collected from questionnaires, while the secondary data were obtained thru related literature and publication. There are 100 respondents participating in this study who was the buyer or user of Oppo Smartphone. The results of this study indicate that celebrity endorser and price has significantly influence the purchasing decision either partially or simultaneously, and the coefficient determination results indicate that Celebrity Endorser and Price affect the Purchase Decision by 15% and the remaining 85% is influenced by other variables that were not discussed in this study.